An Efficient Method for the Synthesis of 5-Aryl Substituted Isoxazoles by Thermolysis of the Related Benzyl and Heteroaromatic Cobaloximes - Tabatabaeian, K.; Mamaghani, M.; Mahmoodi, N.O.; Zaraei, G. (Asian Journal of Chemistry, 2016)
Thermolysis of benzyl- and heteroaromatic methyl cobaloximes in boiling m-xylene, afforded the corresponding 5-arylisoxazoles in moderate to good yields.